Arguing Fundamental Rights - Menéndez, Agustín J.; Eriksen, Erik O. (Law and Philosophy Library, 2006)
Arguing Fundamental Rights explores the path-breaking Theory of Constitutional Rights of Robert Alexy. The critical analysis of the structural elements of Alexy's theory is combined with an assessment of its applied relevance, with special attention being paid to the UK Human Rights Act and the fundamental rights protection in the European Union (before and after the Charter of Fundamental Rights of 2000). The book is unique in combining a challenging interpretation of one the foremost European conceptions of fundamental rights with the discussion of the pragmatics of constitutional adjudication. The chapters combine a focus on key political questions such as whether rights adjudication can be subject to rational assessment and whether judges (and not democratically elected parliaments) should be the umpires of fundamental rights protection, with a concern with key jurisprudential issues, such as the determination of the limits of fundamental rights, the binding effect of fundamental rights to private parties, or whether certain fundamental rights should or should not be regarded as ultimate reasons for action, and as such, could be not be limited, not even when it conflict with other rights. Robert Alexy himself opens the book with an insightful contextualisation of his theory of fundamental rights within his general legal theory. The book is a timely defence of practical reason against claims that emergencies justify trumping fundamental rights.